Relationship between interblink interval and dopamine - Lemon TI (Dove Medical Press, 2013)
Thomas I Lemon, Rupali D ShahSchool of Medicine, Cardiff University, University Hospital of Wales, Cardiff, United KingdomAn interesting study recently reported by Johnston et al1 investigated the interblink interval between dry and normal eye subjects. The authors concluded that this interval was reduced in dry eyes in comparison with normal eyes, that there was a greater variability in interblink intervals in normal eyes, and that the parameters were useful for diagnosis of dry eye disease.1View original paper by Johnston and colleagues